KONSEP MANAJEMEN MUTU PERGURUAN TINGGI KEAGAMAAN ISLAM - Mira Febrina; ISWANTIR M (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Abstract. Improving the quality of Islamic education is an important first step that must be taken. Quality improvement must be carried out comprehensively by using and empowering all aspects of existing resources to become an Islamic Religious Higher Education that is competitive and exists in the midst of global higher education competition. This study is important to carry out to determine the strategic steps of Islamic Religious Higher Education in realizing change in line with the implementation of educational quality components. Research sources come from books, articles, journals that discuss the concept of quality management in higher education institutions. The results of the study are quality control, quality assurance, integrated quality management.